Level of Hypoalbuminemia as a Prognostic Factor in Patients admitted to a Tertiary Care Intensive Coronary Care Unit - Perel, Nimrod; Taha, Louay; Farkash, Rivka; Steinmetz, Yoed; Shaheen, Fauzi; Levi, Nir; Dadon, Ziv; Karameh, Hani; Karmi, Mohamed; Maller, Tomer; Hamyil, Kamal; Turyan, Anna; et al. (Cardiology and Cardiovascular Medicine, 2022)
Introduction: Hypoalbuminemia is common in acute and chronic diseases. It has been proposed as a potential biomarker of frailty, which itself is associated with worse outcomes. However, data regarding the level of hypoalbuminemia and its prognosis in contemporary intensive coronary care unit (ICCU) patients is scarce. Materials and Methods: All patients who had albumin level on admission to an ICCU at a tertiary care center between January 1, 2020, and December 31, 2020, were included in the study. Patients were divided into 3 groups according to their albumin level on admission: low (< 3 g/dL), intermediate (3 g/dL≤ and ≤ 4 g/dL) and high albumin level (> 4 g/dL). Survival and in-hospital interventions and complications were compared. Results: Overall 1,036 consecutive patients were included, mean age was 67±16 years and 70% were males. Of them 88 (8.5%) had low, 739 (71.5%) intermediate and 209 (20%) had high albumin levels. In a multivariate cox proportional hazards analysis, low albumin level was independently associated with higher 1-year mortality rate as compared with high albumin level (HR=9.5; 95% CI: 3.2-25.5, p<0.001). Intermediate albumin level had also a trend toward higher 1-year mortality rate as compared with high albumin level (HR=2.1; 95% CI: 0.9-5.6, p=0.09). Conclusion: Hypoalbuminemia in ICCU patients is a poor prognostic factor associated with in-hospital complications and an independent risk factor for 1-year mortality rate, while intermediate albumin level shows a trend towards higher 1-year mortality rate as well.